1989
DOI: 10.1007/bf00045025
|View full text |Cite
|
Sign up to set email alerts
|

Forest floor biomass, litter fall and nutrient return in Central Himalayan oak forests

Abstract: The seasonal dynamics of forest floor biomass, pattern of litter fall and nutrient return in Central Himalayan oak forests are described. Fresh and partially decomposed litter layers occur throughout the whole year in addition to herbaceous vegetation. The highest leaf litter value is found in April and May and the minimum in September. Partially and largely decomposed litter tended to increase from January to May with a slight decline in June. The wood litter peaked in March and April. The relative contributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
3
7
0
Order By: Relevance
“…However, in the basic nutrients Ca and Mg, our results are higher (annually ca 23.8 kg of Ca and 3.9 kg of Mg), likely due to better soil conditions in both of our study sites. On the other hand, two (or more) times higher values for all mentioned nutrients were found in fertile sites for Q. castaneifolia (Rouhi-Moghaddam et al 2008) or Q. floribunda and Q. lanuginosa (Rawat, Singh 1989). The above-mentioned comparison corresponds with the results of Robert et al (1986), who found site dependent differences in nutrient content and nutrient remobilization in the litterfall of cork oak (Q. suber).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, in the basic nutrients Ca and Mg, our results are higher (annually ca 23.8 kg of Ca and 3.9 kg of Mg), likely due to better soil conditions in both of our study sites. On the other hand, two (or more) times higher values for all mentioned nutrients were found in fertile sites for Q. castaneifolia (Rouhi-Moghaddam et al 2008) or Q. floribunda and Q. lanuginosa (Rawat, Singh 1989). The above-mentioned comparison corresponds with the results of Robert et al (1986), who found site dependent differences in nutrient content and nutrient remobilization in the litterfall of cork oak (Q. suber).…”
Section: Discussionsupporting
confidence: 87%
“…At the same time, the observed relationships were weaker in the case of Halín plot. Therefore, we found a positive relationship between annual lit- (Rawat, Singh 1989;Hernandez et al 1992;Martin et al 1996;Cañellas, San Miguel 1998;Liu et al 2001;Santa-Regina 2001;Ramirez-Correa et al 2007;Rouhi-Moghaddam et al 2008;Perez-Suarez et al 2009;Leon et al 2011). From our observations it is obvious that the inter-annual variability of litterfall amount is relatively high.…”
Section: Discussionsupporting
confidence: 48%
“…(1982) calculated 70~o leaf litter of total litter production in forests around world. In Central Himalayan forests leaf litter fall accounted for 72-86~o (Mehra & Singh 1985;Chaturvedi & Singh 1987;Rawat & Singh 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Pandey (1980) estimated about 87~/o share of leaf litter fall and 13.0~o of wood and miscellaneous litter fall for dry deciduous forest. Chaturvedi & Singh (1987) reported 64-86 ~o of nutrient input by needle litter fall and 14-36 ~o by wood litter fall for a pine forest in Kumaun Himalaya, whereas in the same region in Oak forests, Rawat & Singh (1989) reported 81.3-85~o of nutrient input by leaf litter fall and 15-18.7~o by wood litter fall.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the percentage of total nutrient input through litterfall was found to be 75-85% in leaves, and 10-35% in branches and other parts (including flower, fruit and seed) (Klinge and Rodrigues, 1968;Bernhard-Reversat, 1972;Rawat and Singh, 1989). Similarly, Pandey and Singh (1981) reported that the nutrient input in the oak-coniferous mixed forests was 80-83% through leaves, and 17-20% through branches.…”
Section: Nutrient Contents and Element Flow Of Litter Componentsmentioning
confidence: 94%